Reexamining Meillet's Law - Kapović, Mate (2004)
The primary aim of the paper is to reexamine some of the evidence usually adduced for Meillet's Law. The paper discusses the metatony in o- and i-stem nouns derived from a. p. a verbs and the secondary spread of mobility in i-stems in Slavic. Among other examples, the paper also discusses dialectal Štokavian Sandžak example zvȅ r (a. p. a), Slavic *lȗ bъ and Lithuanian lúobas, which are the outcomes of different PIE ablaut forms, and Slavic *děverь and *sь rdь ce.
Projekt MZOS
ENG